Images of African-American masculinity in hip hop music - Filipová, Petra (Univerzita Pardubice, 2011)
The work deals with depictions of African-American masculinity in hip hop music. It centers on recurrent themes in song lyrics, targeting stereotypes the portrayls reinforce. It attempts to clarify the origin and the background of the stereotypes. The findings are illustrated by multiple examples from song lyrics.
Vyobrazení afro-americké maskulinity v hip hopové hudbě
Keywords: hip hopová kultura; hip hopová hudba; písňové texty; afro-americká mužská identita; afro-americká kultura; stereotypy; hudební průmysl; hip hop culture; hip hop music; rap; lyrics; African-American masculinity; oral; African-American culture; stereotypes; music industry